HUBUNGAN PENGETAHUAN IBU NIFAS TENTANG ASI EKSKLUSIF DENGAN KEBERHASILAN PEMBERIAN ASI - Rosmiati Rosmiati; Dewi Parwati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Exclusive breastfeeding is the provision of breast milk without any additional food or drink from birth to six months of age. The success of exclusive breastfeeding is influenced by various factors, one of which is the mother's level of knowledge regarding the benefits, techniques, and management of breastfeeding. Good knowledge can increase a mother's confidence in breastfeeding and help overcome various obstacles during breastfeeding. This study aims to determine the relationship between postpartum mothers' knowledge about exclusive breastfeeding and successful breastfeeding. This study used a quantitative approach with an observational analytical design using a cross-sectional method. The study sample consisted of 50 postpartum mothers selected using a purposive sampling technique. The research instruments used a knowledge questionnaire about exclusive breastfeeding and an observation sheet for successful breastfeeding. Data analysis was performed using the Chi-Square test. The results showed a significant relationship between postpartum mothers' level of knowledge about exclusive breastfeeding and successful breastfeeding (p < 0.05). Mothers with good knowledge were more likely to successfully breastfeed than mothers with less knowledge. Increasing education about exclusive breastfeeding is an important effort to support successful breastfeeding.